DISCOVERING THE HIDDEN GEMS OF SOPORE, KASHMIR: UNCOVERING THE HISTORICAL SIGNIFICANCE OF MEERAS MAHAL - Ishfaq Ahmad Mir (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Abstract Sopore, Kashmir is known for its natural beauty, but the historical significance of its cultural heritage is often overlooked. Meeraz Mahal is considered a significant cultural heritage site and is an important tourist attraction in Sopore. This paper examines the hidden gem of Sopore, Meeraz Mahal, and its importance in the cultural history of the region. Through a combination of archival research and fieldwork, this study delves into the architectural features and artistic elements of the palace. Furthermore, it explores the social and political context in which Meeraz Mahal was built and how it has been preserved over time. This paper also highlighting the need for the preservation and restoration of historical sites like Meeraz Mahal and its contribution in promotion of tourism and cultural heritage in the region. The building has been featured in several documentaries and films.